The social structure of armed groups. Reproduction and change during and after conflict. (4th July 2018) - Bultmann, Daniel
ABSTRACT: Current research on civil wars and conflict increasingly turns to the inner structure and functioning of state and non-state armed groups and their impact on aspects such as violent practice, internal cohesion and the dissolution of these groups during the conversion to peace. The first aim of this introduction is to set out the theme of this Special Issue on the social structure of armed groups and previous research within the field. The second aim is to introduce the contributions within the Special Issue, alongside possible trajectories of future research on the 'meso-foundations' of civil war and conflict.